Implementing Augmented Reality to Enhance Al-Qur'an Learning Outcomes in Elementary Grade Four - Nurul Azizah; Ulfa Muna Kamila; Rosendah Dwi Maulaya (Proceeding of International Conference on Islamic Boarding School, 2025)
Al-Qur'an is one of the materials at SD Muhammadiyah 1 Paron, this material is important to learn because it can familiarize students with reading, memorizing and knowing the laws of tajweed. Based on observations made by researchers, knowing that the value of al-Qur'an subjects in class 4 has not reached the KKM (70), from the daily exam of 23 children there are 12 children who get scores below 70 and 11 children who are above 70, therefore children who have not reached the KKM are 50% because the method used by the teacher still uses the lecture method which makes students less active. Therefore, the researcher concluded that the learning outcomes of students decreased so that it needed to be improved. Researchers offer augmented reality (AR) learning media in learning al-Qur'an that can present an explanation of the surah properly and correctly. The purpose of this study is to improve the learning outcomes and activeness of students through augmented reality media on Al-Qur'an material in grade 4. The research method used is a class action research (PTK) model of Kemmis and Mc.Taggart which is carried out in two cycles, consisting of planning, implementation, observation and reflection. With research instruments in the form of tests, observations and documentation. The results of the research obtained that the application of augmented reality (AR) learning media can increase the activeness of students with a first cycle percentage of 57% the second cycle increased by 83%, the increase in the first and second cycles is 26%. Likewise, the value of students has increased, namely in the first cycle with a percentage of 74% and in the second cycle an increase of 83%, the difference between the first and second cycles is 9%. This shows that the application of augmented reality (AR) learning media can improve the learning outcomes and activeness of 4th grade students on Qur'an material at Ngawi Muhammadiyah Elementary School.